2018
DOI: 10.1002/ajmg.a.40470
|View full text |Cite
|
Sign up to set email alerts
|

Dual diagnoses in 152 patients with Turner syndrome: Knowledge of the second condition may lead to modification of treatment and/or surveillance

Abstract: Turner syndrome is a sex chromosome abnormality in which a female has a single X chromosome or structurally deficient second sex chromosome. The phenotypic spectrum is broad, and atypical features prompt discussion of whether the known features of Turner syndrome should be further expanded. With the advent of clinical whole exome sequencing, there has been increased realization that some patients with genetic disorders carry a second genetic disorder, leading us to hypothesize that a “dual diagnosis” may be mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 120 publications
0
21
0
Order By: Relevance
“…In addition to associated eye problems that are thought to be directly due to Turner syndrome, women may have a co‐occurring diagnosis, especially X‐linked ocular disorders which manifest in women with Turner syndrome because of the single sex chromosome. Most commonly reported is X‐linked red‐green color blindness, as well as X‐linked retinitis pigmentosum (Jones et al, ; Zhou et al, ), X‐linked juvenile retinoschisis (Jones et al, ) and X‐linked congenital nystagmus. Dual diagnoses with eye problems have included Mendelian syndromes such as blepharophimosis‐ptosis‐epicanthus inversus syndrome (BPES) and Axenfeld‐Reiger syndrome, and a mitochondrial disorder Leber hereditary optic neuropathy (Jones et al, ).…”
Section: Eye Features and Visionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to associated eye problems that are thought to be directly due to Turner syndrome, women may have a co‐occurring diagnosis, especially X‐linked ocular disorders which manifest in women with Turner syndrome because of the single sex chromosome. Most commonly reported is X‐linked red‐green color blindness, as well as X‐linked retinitis pigmentosum (Jones et al, ; Zhou et al, ), X‐linked juvenile retinoschisis (Jones et al, ) and X‐linked congenital nystagmus. Dual diagnoses with eye problems have included Mendelian syndromes such as blepharophimosis‐ptosis‐epicanthus inversus syndrome (BPES) and Axenfeld‐Reiger syndrome, and a mitochondrial disorder Leber hereditary optic neuropathy (Jones et al, ).…”
Section: Eye Features and Visionmentioning
confidence: 99%
“…Most commonly reported is X‐linked red‐green color blindness, as well as X‐linked retinitis pigmentosum (Jones et al, ; Zhou et al, ), X‐linked juvenile retinoschisis (Jones et al, ) and X‐linked congenital nystagmus. Dual diagnoses with eye problems have included Mendelian syndromes such as blepharophimosis‐ptosis‐epicanthus inversus syndrome (BPES) and Axenfeld‐Reiger syndrome, and a mitochondrial disorder Leber hereditary optic neuropathy (Jones et al, ). Growing awareness is essential in order to correctly diagnosis eye problems as more than “just Turner syndrome”.…”
Section: Eye Features and Visionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of clinical whole-exome sequencing, has shown that, some patients with genetic disorders carry a second genetic disorder and dual diagnosis may be more common than suspected of the TS [2]. Of the investigated cases with TS, 80% had mosaicism for TS and dual diagnosis, approximately twice the frequency than in the general TS population [2].…”
Section: Introductionmentioning
confidence: 99%
“…Dual molecular diagnoses involve the distinct or overlapping clinical diagnosis of more than one genetic locus that segregates independently. There are numerous case reports in the literature of patients with co‐occurring genetic disorders (Balci, Hartley, Xi, et al, 2017; Bartoletti‐Stella et al, 2015; Brimble, Pacione, Farrelly, Stevenson, & Ruzhnikov, 2018; Donkervoort et al, 2013; Finsterer, 2020; Finsterer & Zarrouk‐Mahjoub, 2016; Hodapp et al, 2006; Jones, McNamara, Longoni, et al, 2018; Katiyar, Davies, & Goel, 2020; Martin et al, 2014; Masciullo et al, 2013; Murakami, Kimura, Enomoto, et al, 2019; Polavarapu et al, 2019; Posey et al, 2016; Retterer et al, 2016; Ricci et al, 2012; Scarlato et al, 2015; Schreiber et al, 2013; Smith et al, 2019; Splinter et al, 2018; Trujillano et al, 2017; Vona et al, 2018). Complete diagnosis of these cases can pose a challenge as it can be difficult to ascertain if an atypical clinical feature could represent a novel phenotype of the primary condition or are due to a second genetic or acquired disease.…”
Section: Introductionmentioning
confidence: 99%